Analisis Kesalahan Input Kode Belanja terhadap Akurasi Laporan Realisasi Anggaran pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Sikka - Valen Kado, Kristina; Rengga, Andreas; Herdi , Henrikus (Jurnal Projemen UNIPA, 2026)
The implementation of the Regional Government Information System (RGIS) represents a strategic initiative by the government to achieve transparency and accountability in regional financial management. However, the effectiveness of this system is highly contingent upon the quality of initial data input. This study aimed to analyze the phenomenon of expenditure code input errors at the Regional Financial and Asset Management Agency (BPKAD) of Sikka Regency and their subsequent impact on the accuracy of the Budget Realization Report (LRA). Employing a descriptive qualitative methodology, this research utilized data collection techniques including participatory observation, in-depth interviews, and document verification, conducted during an internship in the Accounting Division of BPKAD Sikka Regency. The findings reveal that misclassification between capital expenditures (CAPEX) and goods and services expenditures (OPEX) occurs frequently. This is primarily attributed to the complexity of account nomenclature and the rigid, "centrally locked" nature of the SIPD system. Consequently, these input errors lead to a distortion of information within the LRA and an overstatement of fixed assets on the Balance Sheet. This study concludes that a stringent document verification mechanism within the Accounting Division plays a pivotal role as an internal control to ensure the integrity and reliability of regional financial reports prior to their publication.